Current and magnetic field dependences of a superconducting coplanar waveguide resonator. (11th February 2019) - Kurokawa, H.; Nabeshima, F.; Maeda, A.
Abstract: We fabricated a superconducting coplanar waveguide resonator with leads for dc bias, which enables an ac conductivity measurement under dc bias. The current and magnetic field dependences of resonance properties were measured, and hysteretic behavior was observed as a function of the dc driving current. The observed shifts in the inverse of the quality factor, Q −1, and the center frequency, f 0, were explained by considering both motion of vortices and suppression of the order parameter by the dc current. Our investigation revealed that the strongly pinned vortices have a small influence on f 0, while they still affect Q −1 . Our results indicate that the accurate understanding of the dynamics of driven vortices is indispensable for a control of the resonance properties with a high precision.